2017
DOI: 10.1038/s41598-017-00885-3
|View full text |Cite
|
Sign up to set email alerts
|

Proximate effects of temperature versus evolved intrinsic constraints for embryonic development times among temperate and tropical songbirds

Abstract: The relative importance of intrinsic constraints imposed by evolved physiological trade-offs versus the proximate effects of temperature for interspecific variation in embryonic development time remains unclear. Understanding this distinction is important because slow development due to evolved trade-offs can yield phenotypic benefits, whereas slow development from low temperature can yield costs. We experimentally increased embryonic temperature in free-living tropical and north temperate songbird species to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
(69 reference statements)
1
18
1
Order By: Relevance
“…Additionally, an interaction between date and maternal condition demonstrated that females in good condition consistently created a nest environment that promoted rapid nestling development compared to poor condition females, regardless of environmental conditions. Contrary to expectations from experimental studies (Nord & Nilsson, 2011;Ospina et al, 2018), we found only minimal support are associated with reduced egg temperatures and prolonged incubation periods (Martin, Auer, Bassar, Niklison, & Lloyd, 2007), particularly in cold-adapted species (Ton & Martin, 2017), while experimentally heating tree swallow Tachycineta bicolor nests during the nestling period promotes rapid development (Dawson et al, 2005). We found colder temperatures prolonged the incubation period, as well as, the nestling period, but only when occurring during the late nestling stage.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Additionally, an interaction between date and maternal condition demonstrated that females in good condition consistently created a nest environment that promoted rapid nestling development compared to poor condition females, regardless of environmental conditions. Contrary to expectations from experimental studies (Nord & Nilsson, 2011;Ospina et al, 2018), we found only minimal support are associated with reduced egg temperatures and prolonged incubation periods (Martin, Auer, Bassar, Niklison, & Lloyd, 2007), particularly in cold-adapted species (Ton & Martin, 2017), while experimentally heating tree swallow Tachycineta bicolor nests during the nestling period promotes rapid development (Dawson et al, 2005). We found colder temperatures prolonged the incubation period, as well as, the nestling period, but only when occurring during the late nestling stage.…”
Section: Discussioncontrasting
confidence: 97%
“…Weather conditions can prolong offspring development and the timing of weather events may be critical. Colder ambient conditions are associated with reduced egg temperatures and prolonged incubation periods (Martin, Auer, Bassar, Niklison, & Lloyd, ), particularly in cold‐adapted species (Ton & Martin, ), while experimentally heating tree swallow Tachycineta bicolor nests during the nestling period promotes rapid development (Dawson et al, ). We found colder temperatures prolonged the incubation period, as well as, the nestling period, but only when occurring during the late nestling stage.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the interest in maternal effects in birds, we still have a limited understanding of how environmental factors such as nest predations risk, and life-history traits such as incubation period, impact patterns of maternal resource allocation (but see e.g. Martin 1995;Conway and Martin 2000;LaManna and Martin 2017;Ton and Martin 2017). This is especially true for maternally-derived yolk hormones such as steroid hormones.…”
Section: R a F Tmentioning
confidence: 99%
“…Much of the work on incubation temperature in wild birds has focused on cavity‐nesting species, and/or species with precocial offspring (DuRant et al., ; Hepp, Kennamer, & Johnson, ; Nord & Nilsson, ), primarily because species with these life‐history traits are amenable to temperature manipulation studies. However, the majority of bird species are open‐cup nesting species with altricial young, and to date, little work has been done examining how changes in incubation temperature impact development and survival of open‐cup nesting species with altricial young (but see: Ton & Martin, ). While studies on cavity‐nesting species have provided critical insight into the importance of incubation temperature for proper growth and development (Ardia, Pérez, & Clotfelter, ; Wada et al., ), there are a number of important differences between these species and those that build open‐cup nests and have altricial young.…”
Section: Introductionmentioning
confidence: 99%